Traditional Medicinal Plants for the Prevention and Treatment of Hypertension: A Literature Review - Febyanesti, Athika Reza; Widjanarko, Bagoes; Shaluhiyah, Zahroh (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Background: Hypertension is described as a disease that has a high prevalence in Indonesia. If it is not appropriately treated, it will cause advanced diseases such as stroke, heart failure, and kidney damage. Therefore, it is necessary to prevent and give early treatment, one of which is through alternative routine consumption of herbal medicines.Objectives: This study aims to find out the benefits of herbal medicine for people with hypertension.Methods: The method used in this research is a literature review. It is carried out in several stages by analyzing relevant previous pieces of literature using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) flowchart that illustrates the flow of information through the different phases of a systematic review.Results: A total of 11 reviewed articles show that various herbal plants were obtained with multiple uses to reduce hypertension, and these plants were easy to get and use. It shows that the boiled leaves were the most frequently used part of the plant. Herbal treatment for hypertension aims to enrich antioxidants, block calcium channels, strengthen the endothelium, inhibit ACE, increase without production, and release and decrease biogenic amines. Herbal plants like lemongrass leaves, ginger, gotu kola leaves, and cat's whiskers are useful for lowering blood pressure levels in routine and intensive use without any side effect intervention by boiling.Conclusion: Education regarding herbal plants for hypertension is also beneficial because the increased insight and knowledge they have reduced the possibility of hypertension occurring in the community